Lesson Study Approach: Upaya Meningkatkan Kompetensi Pedagogis Guru melalui Supervisi Klinis di MTs Nurul Ummah Yogyakarta - Suyono (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2020)
This research aims to improve the pedagogical competence of teachers in MTs Nurul Ummah Yogyakarta. This research uses a method of surveillance measures that emphasize on practice, including the actions of plan (planning), do (implementation/implementation) and see (reflection). The results showed that the lesson study can effectively improve the teacher's pedagogical competence. Lesson study activities were able to make teachers open to each other and discuss learning issues in the classroom, and together looking for solutions to the solution. This can be seen from the increased improvement of learning from round to next round. The attendance of the facilitators also helped teachers get enlightened and motivated to innovate innovations in learning.